Becoming a teacher: Experimental evidence from an information intervention - Mariana Alfonso; Matias Busso; Hugo \~Nopo; Antonella Rivera; Triana Yentzen (Inter-American Development Bank (IDB), 2024)
Education systems seeking to improve outcomes must attract, develop, and retain highly effective teachers. A critical challenge is making the teaching profession appealing to talented youth. This paper presents evidence from an experiment in Peru, where we provided high school seniors with information about recent reforms to the teaching career. Wefi nd positive effects on both the extensive and intensive margins: treated students were more likely to enroll in higher education and to choose an education major. These results suggest that career incentives and information can shape not only the current teaching workforce but also future cohorts.
Keywords: I28; I23; J40; O10; 330; Civil service reform; Education policy; Teachers; Information treatment; Randomized control trial; Peru